2019
DOI: 10.5194/acp-19-6059-2019
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation activity of silicates and aluminosilicates in pure water and aqueous solutions – Part 3: Aluminosilicates

Abstract: Abstract. Aluminosilicates and quartz constitute the majority of airborne mineral dust. Despite similarities in structures and surfaces they differ greatly in terms of their ice nucleation (IN) efficiency. Here, we show that determining factors for their IN activity include surface ion exchange, NH3 or NH4+ adsorption, and surface degradation due to the slow dissolution of the minerals. We performed immersion freezing experiments with the (Na-Ca)-feldspar andesine, the K-feldspar sanidine, the clay mineral kao… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(105 citation statements)
references
References 161 publications
(257 reference statements)
9
93
3
Order By: Relevance
“…Arid and semiarid regions are the main sources of mineral dust (e.g., Saharan and Gobi deserts) (Laurent et al, 2006(Laurent et al, , 2008, which can have atmospheric lifetimes of several days (Huneeus et al, 2011). The dust, while being transported, can interact with a variety of trace gases (Usher et al, 2003;Kolb et al, 2010), which can lead to changes in the surface physicochemical properties.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Arid and semiarid regions are the main sources of mineral dust (e.g., Saharan and Gobi deserts) (Laurent et al, 2006(Laurent et al, , 2008, which can have atmospheric lifetimes of several days (Huneeus et al, 2011). The dust, while being transported, can interact with a variety of trace gases (Usher et al, 2003;Kolb et al, 2010), which can lead to changes in the surface physicochemical properties.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Our measurements were collected within a few hours of dust addition, but longer ocean residence times could potentially alter the structure and/or composition of the dust through dissolution and/or disrupting active sites, though Perkins et al (2020) found that incubation in sea salt had little effect upon the IN‐activity of ATD once colligative effects had been considered. However, feldspar is a major contributor to mineral dust INPs, and their ice nucleation activity can be reduced by the presence of aqueous salt (Kumar et al, 2019; Whale et al, 2018), and thus, more investigation is needed to understand the effects of suspension in seawater on the IN‐activity of mineral dust. Seawater also contains small (<0.2 μm) organic ice nucleating entities (INE) from diatom or bacterial exudates that freeze at temperatures ≥ −8°C (McCluskey, Hill, Humphries, et al, 2018; Wilson et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Lithium iodide was found to increase the freezing temperature of kaolinite particles in one study (Reischel and Vali, 1975), but not in a more recent study (Ren et al, 2020). Other inorganic salts including, NaOH and NaCl, decrease the freezing temperatures of some types mineral dusts (Kumar et al, 2019a(Kumar et al, , 2018(Kumar et al, , 2019bReischel and Vali, 1975;Whale et al, 2015). Inorganic acids either decrease the ice nucleation ability of mineral dust particles or have little effect, depending on the type of acid, exposure time, concentration of the acid, and type of mineral dust (Kumar et al, 2018;Burkert-Kohn et al, 2017;Sullivan et al, 2010b;Tobo et al, 2012;Augustin-Bauditz et al, 2014;Wex et al, 2014;Sullivan et al, 2010a;Link et al, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…For comparison purposes, we also investigated the effect of (NH4)2SO4 on the ice nucleating ability of four types of mineral dust (Arizona Test Dust, K-rich feldspar, montmorillonite, and kaolinite). The effect of (NH4)2SO4 on the ice nucleating ability of Arizona Test Dust, K-rich feldspar, and kaolinite, has been studied before (Kumar et al, 2018;Whale et al, 2018;Kumar et al, 2019b), but the effect on montmorillonite has not.…”
Section: Ins Suspensionsmentioning
confidence: 99%